Analisis Pelayanan Keluarga Berencana pada Masa Pandemi COVID-19 di Puskesmas Sidorejo Kota Pagar Alam - Shella Faradista; Lilis Suryani; Helen Evalina Siringo Ringo (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2022)
The essence of national development is the development of Indonesian people as a whole. The high number of population growth can be controlled by implementing family planning. One of the steps to regulate birth is the use of contraception. The purpose of this study was to look at the factors related to family planning services during the COVID-19 pandemic. This study uses a quantitative method with a cross sectional approach. Statistical test using chi square test. Multivariate analysis in this study used multiple logistic regression analysis. In this study, it can be concluded that there is a relationship between education (p = 0.008; OR = 3,231), occupation (p = 0.000; OR = 89.000), parity (p = 0.000; OR = 9.273) with family planning services in the Sidorejo Health Center Work Area, Pagar Alam City. 2021. There is no relationship between the role of officers (p= 1,000), the role of cadres (p= 0.928), age (p= 1,000) with family planning services in the Sidorejo Health Center Work Area, Pagar Alam City in 2021. The most dominant variable is occupation (p = 0.000; OR = 124.967). Suggestions for the findings of this study can be used by health centers, especially in the city of Pagar Alam so that they can pay attention to the respondent's work to do family planning.